A variação entre ter e haver em construções existenciais na fala e na escrita da variedade riopretense - Oliveira, Carolina Sartori de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The researches involving existential ter and haver have shown that existential ter is practically categorical in spoken language. However, in written language haver seems to resist and alternate with ter in existential contexts. The general object of this research conducted in apparent time is to verify if, in the spoken language of São José do Rio Preto, the linguistic change between the existential verbs ter and haver is practically consolidated as it was confirmed in other varieties, indicating categorical levels of ter in the spoken language of São José do Rio Preto. Based on such statement, another point that will be verified is if in the written language of children who attend Junior High School occurs a schooling process which promotes the learning of existential haver, classified as a conservative variant. The theory used in this research is based on the assumptions of the Sociolinguistic Variation developed by Weinreich, Labov and Herzog ([1968] 2006), in which these authors define the language as an object of study used in social contexts and as a heterogeneous object, which differs from the concepts of Saussure ([1916] 1977). Based on this conception of language in use this research analyses two corpora, one of spoken language and another of written language, specifically from children attending Junior High School. The analyses of the data were performed by the Goldvarb statistical program, which provides percentages and relative weights of the linguistic and social group of factors selected to interpret this phenomenon in the São José do Rio Preto’s variety. The results revealed that in spoken language the linguistic groups of factors have an influence on the variation process that includes existential ter and haver, which doesn´t occur in written language, because in this modality just the social group of factors was selected as a conductor of the variation between these existential verbs. The interpretation of the ...

A abordagem do fenômeno de variação entre ter e haver existenciais na literatura especializada tem demonstrado que a forma ter é praticamente categórica na língua falada; no entanto, paradoxalmente, no registro escrito, haver parece resistir e alternar com ter no contexto da construção existencial. Com base em uma distribuição em tempo aparente, este trabalho tem por objetivo geral verificar se, assim como ocorre em outras variedades, o processo de mudança linguística entre as formas ter e haver em contexto existencial está praticamente consolidado, em favor da primeira variante, na língua falada de São José do Rio Preto. Em face da resistência de haver na escrita, este trabalho pretende avaliar também se, na redação de escolares do Segundo Ciclo do Ensino Fundamental, é possível detectar um processo secundário, e puramente escolar, de aprendizagem da forma conservadora haver existencial, ainda considerada uma variante de prestígio. A base teórica em que se assenta este trabalho é o modelo da Sociolinguística Variacionista, especialmente Weinreich, Labov e Herzog ([1968] 2006), que, ao contrário de Saussure ([1916]1977), veem o objeto de estudo como a língua em uso no contexto social, identificando, sobretudo, seu caráter inerentemente heterogêneo. Com base nessa concepção de língua em uso, este trabalho se debruça sobre um córpus de língua falada e um córpus de língua escrita, composto por produções textuais de alunos de 5ª e 8ª séries. Realiza-se uma análise quantitativa dos dados mediante o emprego do programa estatístico Goldvarb, que fornece valores percentuais e pesos relativos para a interpretação qualitativa dos grupos de fatores linguísticos e extralinguísticos selecionados para avaliar esse fenômeno variável na variedade estudada. De um modo geral, os resultados demonstram que, na língua falada, são apenas os grupos de fatores linguísticos que exercem influência no processo de ...
The linguistic variation between existential ter and haver in the spoken and in the written registers of the São José do Rio Preto’s variety
Keywords: Linguística; Análise linguística (Linguística); Sociolinguistica; Linguística de corpus; Língua portuguesa - Variação; Língua portuguesa (Ensino fundamental); Língua portuguesa - São José do Rio Preto (SP); Linguistic analysis (Linguistics)